Expectations of iPad Use in an Internal Medicine Residency Program: Is It Worth the "Hype"? - Luo, Nancy; Chapman, Christopher G; Patel, Bhakti K; Woodruff, James N; Arora, Vineet M (JMIR Publications, 2013)
BackgroundWhile early reports highlight the benefits of tablet computing in hospitals, introducing any new technology can result in inflated expectations. ObjectiveThe aim of the study is to compare anticipated expectations of Apple iPad use and perceptions after deployment among residents. Methods115 internal medicine residents received Apple iPads in October 2010. Residents completed matched surveys on anticipated usage and perceptions after distribution 1 month prior and 4 months after deployment. ResultsIn total, 99% (114/115) of residents responded. Prior to deployment, most residents believed that the iPad would improve patient care and efficiency on the wards; however, fewer residents "strongly agreed" after deployment (34% vs 15% for patient care, P<.001; 41% vs 24% for efficiency, P=.005). Residents with higher expectations were more likely to report using the iPad for placing orders post call and during admission (71% vs 44% post call, P=.01, and 16% vs 0% admission, P=.04). Previous Apple iOS product owners were also more likely to use the iPad in key areas. Overall, 84% of residents thought the iPad was a good investment for the residency program, and over half of residents (58%) reported that patients commented on the iPad in a positive way. ConclusionsWhile the use of tablets such as the iPad by residents is generally well received, high initial expectations highlight the danger of implementing new technologies. Education on the realistic expectations of iPad benefits may be warranted.